Integration of Ecological and Socio-Economic Aspects for Sustainable Management of Nambo Beach Tourism - Wa Ode Hastiani Fahidu; Lies Indriyani; La Ode Siwi; Agusrinal; La Gandri; Sahindomi Bana; La Ode Muhammad Erif -; Ajis Safarudin (Jurnal Serambi Engineering, 2026)
Managing coastal tourist areas requires an approach that can integrate ecological and socio-economic aspects so that environmental quality and community welfare are maintained. This study aims to analyze the ecological and socio-economic conditions in the Nambo Beach Tourism Area, Kendari City, and to formulate sustainable management strategies through an integrative ecology–social approach. The research was conducted in October–November 2025 through field surveys, water quality measurements (temperature, pH, salinity, DO, BOD, TSS, TDS), vegetation cover analysis based on the 2024 SHP, observations, as well as interviews and questionnaires with the community. The results show that most water quality parameters still meet marine tourism standards, although there is pressure on the TSS value (96 mg/L) and indications of increasing organic material shown by the BOD value (3.70 mg/L). Coastal vegetation cover, including mangroves, still dominates with an area of 5,910 hectares. but it’s starting to be pressured by increased tourism activities and development. On the socio-economic side, the community relies on income from tourism businesses, small trade, and transportation, but they face challenges such as low environmental awareness, limited public facilities, and suboptimal waste management. The integration of analyses using the ICM and SWOT approaches shows that Nambo Beach is in the aggressive strategy quadrant, meaning it has great potential for development.